Parent training for feeding problems in children with autism spectrum disorder: A review of the literature. Issue 2 (3rd April 2019) - Aponte, Courtney A.; Brown, Kimberly A.; Turner, Kylan; Smith, Tristram; Johnson, Cynthia
ABSTRACT: A scoping review of the literature was conducted to identify published studies in which parents of children with Autism spectrum disorder (ASD) were trained to implement interventions designed to improve their child's feeding and mealtime behaviors. Twenty-six studies were included in the review. Of these, 23 used single subject designs, and 3 used group designs. All reported improvements in target behaviors (usually acceptance of novel foods or reduction in disruptive mealtime behavior). However, only 3 described a procedure for incorporating parent input into the intervention plan; 7 directly measured parents' fidelity in implementing intervention procedures; and 7 assessed social validity or parent satisfaction. Thus, there is a need for more systematic involvement of parents in treatment for feeding in children with ASD and more comprehensive outcome assessment.